An Integrated Approach for the Efficient Extraction and Solubilization of Rice Microsomal Membrane Proteins for High-Throughput Proteomics - Nguyen, Truong Van; Gupta, Ravi; Annas, Dicky; Yoon, Jinmi; Kim, Yu-Jin; Lee, Gi Hyun; Jang, Jeong Woo; Park, Kang Hyun; Rakwal, Randeep; Jung, Ki-Hong; Min, Cheol Woo; Kim, Sun Tae (Frontiers in Plant Science, 2021)
The preparation of microsomal membrane proteins (MPs) is of critical importance to microsomal proteomics. To date, the isolation of MPs has relied majorly on ultracentrifugation-based methods and the subsequent solubilization of isolated MPs. However, these approaches are labor-intensive, time-consuming, and unaffordable at times. Moreover, the use of SDS and its removal prior to mass spectrometry (MS) analysis through multiple washing steps results in the loss of proteins. To address the above limitations, we introduce a simple micro-centrifugation-based MP extraction (MME) method from rice leaves. The efficacy of this approach was compared with a commercially available plasma membrane extraction kit (PME), and the subsequent solubilization of isolated MPs in a MS-compatible surfactant, 4-hexylphenylazosulfonate (Azo), and SDS was assessed using a label-free proteomic approach. Results validated the effectiveness of the MME method, specifically in the enrichment of plasma membrane proteins as compared with the PME method. Further, Azo showed several advantages over the SDS in solubilizing the MPs as reflected by label-free quantitative proteome analysis. Altogether, this research provides a relatively simple and rapid workflow for the efficient extraction of MPs with an Azo-integrated MME approach for bottom-up proteomics.